EXTENSIVE MAXILLOFACIAL LYMPHANGIOMA WITH SUPPURATION IN THE LATE POSTNATAL PERIOD OF A CHILD - P.I. Tkachenko; M.O. Cholovskyi; O.B. Dolenko; N.M. Lokhmatova; N.M. Korotich (Український стоматологічний альманах)
Lymphangiomas have a dysontogenetic origin, that is, they occur during the development of the fetus and are treated as an abnormal development of the endothelium of proliferating lymphatic vessels and manifest clinically, most often immediately after the birth of a child or in infancy.